Arsenomics of exiguobacterium sp PS (NCIM 5463) - Sacheti, Poonam; Bhonsle, Hemangi S.; Patil, Rajendra; Kulkarni, Mahesh J.; Srikanth, Rapole; Gade, Wasudeo N. (RSC Advances, 2013)
In the present study, arsenate [As(V)] tolerant organisms were isolated from a metal contaminated site, and identified by 16S rDNA sequencing as Exiguobacterium sp. Arsenomics (omics of arsenic response) in Exiguobacterium sp. PS via two-dimensional gel electrophoresis (2-DGE) coupled with identification of proteins using MALDI-TOF MS, MALDI-TOF MS/MS and LC/MSE are studied vide this paper. Out of 2460 Coomassie stained proteins, 270 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 45 spots (proteins) were subjected to MALDI-TOF MS/MS, MALDI-TOF/TOF and LC/MSE. Out of these, 33 were identified and categorized into several functional categories (including both known and novel/putative stress responsive proteins) viz., carbohydrate and energy metabolism, stress response, motility, amino acid, and purine and protein synthesis. The identifications of unique proteins, phosphate ABC transporter ATPase subunit and pyridine nucleotide disulfide oxidoreductase, are the significant findings of the present study which may be used as markers of As(V) stress in Exiguobacterium sp. PS. The absence of As(V) reductase activity and non-amplification of the arsC gene of the ars operon suggests that the classical mechanism of As(V) resistance may not be operating in Exiguobacterium sp. PS. Lastly, considering the fact that proteomic studies under As(V) stress were performed only in Gram negative organisms, this study is the first comprehensive endeavour to explore the mechanism of As(V) response in Gram positive organisms, Exiguobacterium sp. PS at the proteomic level.

Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics